2019
DOI: 10.33584/jnzg.2019.81.397
|View full text |Cite
|
Sign up to set email alerts
|

Modelling long-term changes in soil phosphorus and carbon under contrasting fertiliser and grazing management in New Zealand hill country

Abstract: Soil carbon (C) stocks under permanent New Zealand pastures vary with slope and aspect due to differences in primary production, animal behaviour and nutrient return. An existing nutrient transfer model was extended using a web-based, general-purpose modelling tool to simulate long-term changes in soil phosphorus (P) and C in hill country under contrasting fertiliser and sheep stocking regimes. Three self-contained farmlets were examined: no P applied; 125 kg single superphosphate (SSP)/ha/year; and 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…For example, dung P is the prevalent pathway for animal returns to grazed pastures (Haynes and Williams 1993). This is far from being evenly distributed on the landscape (Bilotto et al, 2019); rather, it is returned in small areas at high concentrations (Gillingham, 1980). The concentration of P in dung from grazing ruminants is often much greater than in the herbage consumed, and has been reported to be up to a four-fold greater (Shand and Coutts 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dung P is the prevalent pathway for animal returns to grazed pastures (Haynes and Williams 1993). This is far from being evenly distributed on the landscape (Bilotto et al, 2019); rather, it is returned in small areas at high concentrations (Gillingham, 1980). The concentration of P in dung from grazing ruminants is often much greater than in the herbage consumed, and has been reported to be up to a four-fold greater (Shand and Coutts 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Published sheep dung disappearance rates differ considerably, since factors, such as local climate, soil conditions, and dung consistency, alter decomposition (Williams and Haynes 1995;Shand and Coutts 2006;Bahamonde et al, 2017). Modelling efforts to capture long-term soil phosphorus (P), organic carbon (C) and nitrogen (N) dynamics under hill country grazing have shown that animal dung is an important contributor to the flux of P, C and N through these systems (Hoogendoorn et al, 2011;Bilotto et al, 2019). However, there is a lack of information on the integration of biological and topographic drivers of nutrient cycling in these complex landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Where P is deposited by cattle may greatly influence its retention within the pastures. In their study on grazed pastures, under contrasting grazing management and fertilizer applications, Bilotto et al [20] reported greater mean annual changes in soil P on low slopes in comparison to high and medium slopes attributing the difference to movement of phosphorus in animal dung from higher slopes to the lower slopes. Nellesen et al [21] indicated greater loss of P from pastures with unrestricted stream access compared to pastures with restricted stream access.…”
Section: Introductionmentioning
confidence: 96%
“…Modelling efforts to capture long-term soil nutrient dynamics under hill country grazing in New Zealand have been reported (Saggar et al 1990;Hoogendoorn et al 2011), but none of these reports capture the complex relationships between soil P, SOC and N stocks in soil and their interaction with topography. To account for some of these factors, Bilotto et al (2019) built a spatial, process-based P and C cycling model following the P and sulphur (S) model of Saggar et al (1990) and the C and N models by Hoogendoorn et al (2011). In addition to slope, the model developed by Bilotto et al (2019) accounted for aspect [the main compass direction (East, Northwest, Southwest) that each slope faces], increased soil depth (from 150 to 300 mm) to better account for P movement down the profile (Mackay and Costall 2016), and to explore temporal changes in P and SOC stocks and flows in these systems over time.…”
Section: Introductionmentioning
confidence: 99%
“…To account for some of these factors, Bilotto et al (2019) built a spatial, process-based P and C cycling model following the P and sulphur (S) model of Saggar et al (1990) and the C and N models by Hoogendoorn et al (2011). In addition to slope, the model developed by Bilotto et al (2019) accounted for aspect [the main compass direction (East, Northwest, Southwest) that each slope faces], increased soil depth (from 150 to 300 mm) to better account for P movement down the profile (Mackay and Costall 2016), and to explore temporal changes in P and SOC stocks and flows in these systems over time. The addition of aspect, extra soil depth and time components allowed for an improved prediction of P dynamics compared with the original model of Saggar et al (1990).…”
Section: Introductionmentioning
confidence: 99%